Prirodni propulzori - Dadić, Ivan; Dadić, Vlado (Promet - Traffic&Transportation, 2012)
This paper deals with an as efficient as possible conversion of energy of human rustles and different types of piston and rotation engines by way of devices given the common name of propulsions, by means of specially designed surfaces which in the process of rotation create an almost maximum driving force. The basic structure of these natural propulsions i.e. surfaces is a curve in the plane which is delineated by the particle of the matter which is due to the rotation affected by the centrifugal and tangential force i.e. their resultant as well as the curve vertical on to it. Research of natural propulsion refers us to the research of natural eccentricity or disbalance in general that may prove of influence on the design of cylinder and electric machines and have further repercussions on the design of different types and shapes of craft and vessel.